Dielectric Study of PVC-LiF Composites Films - Ahmad A. Hasan (Iraqi Journal of Science, 2021)
PVC-LiF composites films with different lithium fluoride (LiF) concentrations (0, 30, 50, and 70 weight %) were prepared by using the casting method. This research deals with the investigation of dielectric properties for PVC-LiF composite films as a function of frequency and temperature in the ranges of 100 to 107 Hz and 293 - 370 K, respectively. The A.C activation energy values estimated from Arrhenius equation were 0.03820, 0.3174, 0.2009, and 0.1845 eV for the different PVC-LiF films with different LiF concentrations, respectively. It was found that the activation energy decreases by increasing LiF concentration and frequency. The exponent (s) showed a progressive increase with LiF for PVC-LiF films, while it showed a non-systematic sequence with the increase of temperature. The dependence of the dielectric constant (εr) and dielectric loss (εi) on temperature and frequency was investigated for PVC-LiF films with the different LiF concentrations. The dielectric spectrum showed a strong dispersion when LiF was added to the polymer matrix (PVC) in the whole range of frequency and temperature. The results were interpreted in terms of structural differences caused by the effect of thermal treatment.